Changes in body mass index and its association with socio-demographic characteristics between 2010 and 2016 in Singapore - Yunjue Zhang; Edimansyah Abdin; Rajeswari Sambasivam; Saleha Shafie; Kumarasan Roystonn; Janhavi Ajit Vaingankar; Siow Ann Chong; Mythily Subramaniam (Frontiers in Public Health, 2024)
BackgroundEpidemiological studies have observed an increase in the prevalence of obesity in both western and Asian countries. This study aims to compare the distribution of body mass index (BMI) in the general population of Singapore between 2010 and 2016, and to explore the socio-demographic risk factors associated with it.MethodsData for this study were extracted from two national-wise studies in 2010 and 2016, two population-based, cross-sectional epidemiological studies. BMI cut-off scores were used as an indicator to assess obesity in this study, and the data included in the analysis was self-reported by the respondents.ResultsOverall, the study observed decreasing prevalence in underweight and normal weight categories; and an increasing prevalence in overweight and obesity categories in the Singapore adult population between 2010 and 2016. Age, gender, ethnicity, marital status, and educational level were found to be significantly associated with BMI categories.ConclusionThe observed increase in the population’s BMI between 2010 and 2016 may lead to an increase in the incidence of chronic diseases in Singapore. Our study findings add to the existing local literature and provides data for evidence-based policymaking on health-related interventions and program planning.